2017
DOI: 10.1088/1742-6596/824/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students’ Initial Ability in Understanding Phylogenetic Tree

Abstract: Abstract. The Phylogenetic tree is a visual representation depicts a hypothesis about the evolutionary relationship among taxa. Evolutionary experts use this representation to evaluate the evidence for evolution. The phylogenetic tree is currently growing for many disciplines in biology. Consequently, learning about the phylogenetic tree has become an important part of biological education and an interesting area of biology education research. Skill to understanding and reasoning of the phylogenetic tree, (cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The needs analysis results can be used as the primary reference for developing the product and its specifications Evolution is a branch of biological science that investigates the process of biological change in which each species accumulates character differences obtained from their ancestors as they adapt to different environments over time (Urry et al, 2020). As for phylogeny, it is the study of the evolution history of a species or group of species visualized through phylogenetic trees (Solomon et al, 2019). Sa'adah et al (2017) & Fuadiyah et al (2021 revealed that the majority of students have difficulty understanding phylogeny, which is based on the low ability of students to interpret phylogenetic trees so that the right solution is needed to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%
“…The needs analysis results can be used as the primary reference for developing the product and its specifications Evolution is a branch of biological science that investigates the process of biological change in which each species accumulates character differences obtained from their ancestors as they adapt to different environments over time (Urry et al, 2020). As for phylogeny, it is the study of the evolution history of a species or group of species visualized through phylogenetic trees (Solomon et al, 2019). Sa'adah et al (2017) & Fuadiyah et al (2021 revealed that the majority of students have difficulty understanding phylogeny, which is based on the low ability of students to interpret phylogenetic trees so that the right solution is needed to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%
“…These fallacies in understanding the concepts of phylogeny and evolution seem to be rather hard to overcome. Even university students of biology often showed these misconceptions while dealing with the phylogenetic trees (Dees et al, 2014;Halverson et al, 2011;Kummer et al, 2016) -they were unable to correctly interpret the relations between taxa (Phillips et al, 2012;Sa'adah et al, 2017;Sandvik, 2008) and showed a wrong understanding of evolution (Sa'adah et al, 2017). Both biology graduates and undergraduates tended to read the phylogenetic trees from left to right assuming that organisms on the left always show more ancestral traits (Novick et al, 2012;Omland et al, 2008).…”
Section: Introductionmentioning
confidence: 99%